DYNAMICS OF DENGUE HEMORRHAGIC FEVER INCIDENCE WITH SPATIO-TEMPORAL APPROACH IN MARITENGNGAE SUBDISTRICT, SIDENRENG RAPPANG DISTRICT, SULAWESI SELATAN PROVINCE, IN 2008-2009 - I Made Swastika; Tri Baskoro Tunggul Satoto; Anis Fuad (Tropical Medicine Journal, 2011)
Introduction: Dengue Hemorrhagic Fever (DHF) causes 40% of world population at risk for infection, and 50 million people get infection with as many as 24,000 die every year. Incidence rate in Indonesia, particularly in Maritengngae Subdistrict, Sidenreng Rappang District, is increasing and needed to be controlled. Disease distribution has not been documented regionally. The dynamics of the incidence,that comprises the characteristics of the patient, environmental conditions, susceptibility of mosquitoes resulted from insecticide use, transovarial infectivity, and the incidence pattern were unknown.Objectives: To identify the dynamics of DHF incidence with spatio-temporal approach, includes gender, age, the habit of cleaning the water containers, house density, the density of water containers within the radius of 100 meters from the house of the patient, resistance of the mosquito, and transovarial transmission of Dengue virus.Methods: Subjects were DHF patients in Maritengngae Subdistrict. It was an epidemiological observational study with cross-sectional design and spatio-temporal approach to variables of the study, which included the patient characteristics (age, gender, habit of cleaning the water containers), environmental conditions (house density, water container density within 100 meter radius around the patient’s house), and vector conditions (resistance status to organophosphate insecticide, and transovarial transmission of Dengue virus).Results: Cases of DHF in Maritenggae Sub district, Sidenreng Rappang District, South Sulawesi decreased from 95 cases in 2008 to 38 cases in 2009, except in Kelurahan Majeling. Incidence distribution of DHF in 2008-2009 based on gender were not different (p=1.000), patients with age <15 years old were different from age ≥15 years (P=0.016 and p = 0.013), house density and density of water containers around the patient’s house were not different (p=0.829 and p = 0.538). The habit of cleaning water containers at the house was 43.84%. There were 1.94% of Aedes aegypti samples showed medium resistance (tolerance) status against organophosphat insecticide and 33.33% of samples showed transovarial transmission of Dengue virus. The highest of transovarial transmission occured in Kelurahan Majeling with transovarial transmission index of 100%.Conclusion: The transmission dynamic of DHF in Maritengngae sub district is not influenced by gender, house densities, water container densities, and the frequency of source reduction, but influenced by ages. Most of Ae. aegypti mosquitoes are still susceptible against organophosphate insecticides. The highest of transovarial transmission of dengue virus in Ae. aegypti in Kelurahan Majeling with Transovarial transmission index of 100% may contribute in the increasing of DHF cases in the Kelurahan Majeling in 2009.Keywords: dynamics, dengue, spatio-temporal, Ae. aegypti, Maritengngae.